Supernaturally - White, Kiersten (New York : HarperTeen, 2011)
Evie thinks she has left the International Paranormal Containment Agency, and her own paranormal activities, behind her when she is recruited to help at the Agency, where she discovers more about the dark faerie prophecy that threatens her future.
Keywords: Supernatural -- Fiction; Fairies -- Fiction; Prophecies -- Fiction; Identity (Psychology) -- Fiction